Commodity Prices, Wages and US Inflation in the Twentieth Century - Bloch, Harry; Dockery, Alfred Michael; Sapsford, D. (ME Sharpe, 2004)
We consider the impact of primary commodity prices and wages on U.S. inflation in the context of markup pricing. We estimate separate equations for world commodity prices, wage rates, and domestic finished goods prices using annual data for 1900 to 2001. We find complete pass-through of commodity prices and wages into inflation of finished goods prices, with both input prices having a positive and statistically significant impact. Demand has a direct negative impact on finished goods prices, a delayed and temporary positive impact on wages (through the unemployment rate), and a strong positive impact on primary commodity prices.